Mesh cancer: long-term mesh infection leading to squamous-cell carcinoma of the abdominal wall - Birolini, C.; Minossi, José Guilherme [UNESP]; Lima, C. F.; Utiyama, E. M.; Rasslan, S. (Springer Nature, 2013)
Purpose: It is recognized that chronic inflammation can cause cancer. Even though most of the available synthetic meshes are considered non-carcinogenic, the inflammatory response to an infected mesh plays a constant aggression to the skin. Chronic mesh infection is frequently the result of misuse of mesh, and due to the challenging nature of this condition, patients usually suffer for years until the infected mesh is removed by surgical excision. Methods: We report two cases of squamous-cell carcinoma (SCC) of the abdominal wall, arising in patients with long-term mesh infection. Results: In both patients, the degeneration of mesh infection into SCC was presumably caused by the long-term inflammation secondary to infection. Patients presented with advanced SCC behaving just like the Marjolin's ulcers of burns. Radical surgical excision was the treatment of choice. The involvement of the bowel played an additional challenge in case 1, but it was possible to resect the tumor and the involved bowel and reconstruct the abdominal wall using polypropylene mesh as onlay reinforcement, in a single stage operation. He is now under adjuvant chemotherapy. The big gap in the midline after tumor resection in case 2 required mesh bridging to close the defect. The poor prognosis of case 2 who died months after the operation, and the involvement of the armpit, groin and mesenteric nodes in case 1 shows how aggressive this disease can be. Conclusion: Infected mesh must be treated early, by complete excision of the mesh. Long-standing mesh infection can degenerate into aggressive squamous-cell carcinoma of the skin. © 2013 Springer-Verlag France.
Keywords: Enterocutaneous fistula; Mesh infection; Squamous-cell carcinoma; Synthetic mesh